Hubungan Siklus Hidup Perusahaan dan Manajemen Laba: Good Corporate Governance sebagai Variabel Moderating - Suwarno Suwarno (JIATAX (Journal of Islamic Accounting and Tax), 2020)
The purpose of this study is to determine the relationship of the corporate life cycles to earnings management and analyze Good Corporate Governance to moderate the relationship between the corporate life cycles with earnings management. This research use as quantitative approach using secondary data. The sampling technique uses purposive sampling method. The total sample used in this study were 75 company samples. The analysis technique used in this study is the Structural Equation Modeling-Partial Leasr Square (SEM-PLS) method using WarpPLS Version 5.0 Software. The results showed that the company’s life cycle variables influence earnings management and GCG can moderate the company’s life cycle relationship with earnings management so as to waked earnings management actions.